2008
DOI: 10.1002/app.27612
|View full text |Cite
|
Sign up to set email alerts
|

Effective thermal conductivity behavior of filled vulcanized perfluoromethyl vinyl ether rubber

Abstract: The effective thermal conductivity behavior of vulcanized perfluoromethyl vinyl ether (PMVE) rubber filled with various inorganic fillers was investigated and analyzed with thermal conductivity models. Experimental results showed that there was no significant improvement in the thermal conductivity of PMVE rubber if the intrinsic thermal conductivity of the fillers was greater than 100 times that of the rubber matrix, and this agreed with the prediction of Maxwell's equation. The thermal conductivity of PMVE r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For instance, the temperature in lip seals working in hostile environments may be as high as 185°C. Therefore, elastomer nanocomposites with high ageing resistance and high thermal conductivity are required for these applications [254,255]. The high heat build-up generated during the use of a tire is dangerous in that it will degrade the mechanical performance of the tire.…”
Section: High-speed Dynamic Elastomeric Productsmentioning
confidence: 99%
“…For instance, the temperature in lip seals working in hostile environments may be as high as 185°C. Therefore, elastomer nanocomposites with high ageing resistance and high thermal conductivity are required for these applications [254,255]. The high heat build-up generated during the use of a tire is dangerous in that it will degrade the mechanical performance of the tire.…”
Section: High-speed Dynamic Elastomeric Productsmentioning
confidence: 99%
“…And the third way is to transfer the generated heat from inside to outside. Much research works on thermal conductivity of rubber composites have been done [1][2][3][4][5][6][7][8], however, there are rather few reports dealing with the applications in tires [9][10][11]. Wang et al [9] indicated that nano-zinc oxide could not only reinforce ethylene propylene diene monomer (EPDM) but also improve thermal conductivity significantly, and the composites could serve in dynamic conditions with longer expected service life.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal conductivity is even discussed as a function of polymer/graphite composition parameters. [12][13][14][15][16][17] Agari et al [18] prepared a kind of polyethylene/graphite composite with a component of 20 vol% filler and a thermal conductivity of 1.53 W/ m K. They also investigated the effect of different dispersion methods on thermal behavior of the composites. Hung et al's research [19] on the thermal interface resistance of polymer nanocomposites reinforced with graphite nanoplatelets was also remarkable.…”
Section: Introductionmentioning
confidence: 99%